Resistance mechanisms and cross-resistance for a pyridine-pyrimidine amide inhibitor of microtubule polymerization. Issue 13 (1st July 2019) - Fox, J. Chancellor; Evans, Alex T.; Blomfield, Michael P.; Livingstone, Scout K.; Tenney, Stephen R.; Webster, Jace B.; Perry, Katelyn; Hill, Jonathon T.; Bikman, Benjamin T.; Hansen, Marc D.H.
Graphical abstract: Abstract: Despite their clinical importance, drug resistance remains problematic for microtubule targeting drugs. D4-9-31, a novel microtubule destabilizing agent, has pharmacology that suggests it can overcome common resistance mechanisms and has been shown to remain efficacious in cell and animal models with acquired taxane resistance. To better understand resistance mechanisms and the breadth of cross-resistance with D4-9-31, this study examines the A2780 ovarian cancer cell line as it develops acquired resistance with continuous exposure to D4-9-31. Analyzing cellular responses to D4-9-31 reveals that D4-9-31 resistance is associated with increased mitochondrial respiration, but no cross-resistance to other microtubule targeting agents is observed. Sequencing of transcripts of parental cells and resistant counterparts reveals mutations and altered expression of microtubule-associated genes, but not in genes commonly associated with resistance to microtubule targeting drugs. Additionally, our findings suggest distinct mechanisms drive short- and long-term drug resistance.